An evaluation of listening task complexity in the coursebook New Headway Pre- intermediate to the non-English major students at Hanoi University of Industry - Bùi, Phương Thảo (ĐHNN, 2017)
Part 1: Introduction. Part 2: Development: Chapter 1: Literature Review; Chapter 2: Methodology; Chapter 3: Findings and Discussions. Part 3: Conclusion